Technical efficiency in Chile's water and sanitation providers - Ferro, Gustavo Adolfo (2016)
Chile achieved universal levels of coverage in water, sewerage and wastewater treatment in urban areas. The providers show complete cost recovery, universal metering and diminishing consumption. But investments in Non-Revenue Water control have been deemed insufficient. We explore the sector's comparative technical efficiency, in recent years, and address new challenges related to Non-Revenue Water reduction. We find that a 10 percent reduction in Non-Revenue Water implies a 2.6 percent increase in the input vector. Regulators can induce providers to invest more by recognizing the increased costs, and influence efficiency gains sharing with clients, including automatic coefficients in the rate formula.